The Influence of Structural Stiffness and Ice Shape on Impact Loads in Ice-Structure Interaction Experiments - Müller, Franciska; von Bock und Polach, Rüdiger Ulrich Franz; Ehlers, Sören (American Society of Mechanical Engineers, 2024)
Ships that are navigating in waters with ice occurrence are prone to the risk of damage due to ice impact. For assessing the safety of ships it is crucial to predict these loads accurately. Ship hulls have varying structural stiffness due to differences in structural design. The stiffness influences the deformation of the structure during ice impact, which in turn affects both the failure behavior of the ice and the loads experienced by the structure. The aim of this study is to understand how ice responds to variations in structural stiffness in an impact scenario and how the structure is affected by impacting with different ice shapes as well as the interplay of both. Research on this topic is very limited, therefore we seek to address this knowledge gap. This paper presents controlled drop tower experiments with freshwater granular ice of varying shapes impacting structures with different levels of stiffness. Drawing upon prior experience,five different ice shapes were investigated: dome, 10° cone, 30° cone, 30° truncated cone and cylinder. Each of these ice shapes impacted both a quasi-rigid plate and a 3 mm steel plate.The 3 mm plate underwent plastic deformation and was measured before and after the ice impact. The data analysis showcased a significant reliance of the peak load on both the structural stiffness and the shape of the impacting ice. Additionally, the analysis highlighted the considerable impact of ice shape on the magnitude of the maximum plastic deformation in experiments involving ice specimens colliding with the 3 mm plates. Among the ice shapes investigated, the dome-shaped and truncated cone specimens stand out, producing the most pronounced plastic deformation in the plate. The results of this study contribute to the development of predictive numerical models for ice impacts on structures by providing a robust set of validation data.